Ischemic Monomeric Neuropathy in a Woman with Sickle Cell Anaemia - Alexandra Agapidou; Laura Aiken; Lisa Linpower; Dimitris A. Tsitsikas (Case Reports in Hematology)
Sickle cell disease is an inherited haemoglobinopathy that can affect multiple organs and systems. The most common neurological complication in sickle cell disease is stroke and silent cerebral infarcts. Peripheral nervous system involvement has been described but is exceedingly rare. Herein, we describe the case of a young woman who presented with acute flaccid paralysis and sensory loss of the left lower extremity in the context of a painful vasoocclusive crisis which resolved rapidly after receiving an emergency automated red cell exchange transfusion.